2021 Guidelines for Operation and Usage of County Kitchens in the State of Florida - Amarat Simonne; Tim Wilson; Geralyn Sachs; Chris Hilliard; Steven von Bodungen; Liz Felter (EDIS, 2021)
Many county Extension office buildings have small kitchens or areas for food preparation to accommodate employees, group educational events, and other mission-related activities.